Application of satellite observations in conjunction with aerosol reanalysis to characterize long-range transport of African and Asian dust on air quality in the contiguous U.S. (August 2018) - Chen, Sheng-Po; Lu, Cheng-Hsuan; McQueen, Jeffery; Lee, Pius
Abstract: A methodology utilizing multiple aerosol measurements and reanalysis was developed to analyze the long-range transport (LRT) of North African and Asian dust events and their effect on contiguous U.S. (CONUS) air quality. Two events in 2015, that originated inland from North Africa and Asia, were detected with aerosol optical depth (AOD) greater than 0.8 over the Gulf of Mexico (June 21) and west coast of Oregon and Washington (April 19). Large amounts of dust were rising over Sahara-Sahel and Taklamakan deserts during these events. For the North African dust event, dust remained the dominant aerosol species transporting from North Africa to CONUS. For Asian dust, before the Taklamakan dust outbreak traveled across the Pacific Ocean, it mixed with sulfate from East China and organic carbons from Siberia. The trans -Atlantic North African dust emerged and compressed below 5 km over the Azores High, whereas the trans -Pacific Asian dust entered the westerlies (5–10 km) along with the mid-latitude frontal system. For the two cases examined, the North African dust event tended to have more influence on CONUS air quality. During the LRT periods, there were 4 of 17 rural and suburban stations (with AOD > 0.5 as the LRT dust approached) in Texas and Louisiana reporting PM2.5 daily maximum observations greater than 36.3 μg m −3 . In contrast, the Asian dust stayed above ground level, and all of the 4 rural and suburban stations (with AOD > 0.5 as the LRT dust approached) in Washington and Oregon observed daily maximum PM2.5 below 22.4 μg m −3 . The integration of measurements and modeling was able to successfully characterize the sources and transport patterns of the LRT dust events, and differentiate their influence on CONUS air quality. Even though there was high AOD from the Asian LRT dust detected over the western CONUS, significant impacts on surface air quality was not observed as the dust remained aloft. Graphical abstract: Image 1 Highlights: A methodology was tested for investigating two dust events from North Africa and Asia to U.S. Sources, long-range transport properties and the air quality impact on U.S. were investigated. The long-range transport of North African dust tended to have more influence on air quality. Abstract : Capsule: The integration of multiple measurements with model simulations was an effective approach with which to assess the long-range transport of dust storms and their impact on contiguous U.S. air quality.